y=-6.1(20)-46.9

Simple and best practice solution for y=-6.1(20)-46.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-6.1(20)-46.9 equation:



y=-6.1(20)-46.9
We move all terms to the left:
y-(-6.1(20)-46.9)=0
We add all the numbers together, and all the variables
y-(-53.02)=0
We add all the numbers together, and all the variables
y+53.02=0
We move all terms containing y to the left, all other terms to the right
y=-53.02

You can always share this solution

See similar equations:

| h(20)=-6.1(20)-46.9 | | 5(-7y+8)+y=-28 | | 6x-9=4x+8 | | 2x-3/4=x+2/3 | | 3+56z? =6 | | 27^4x=9^x+4 | | 27^4x=9^x+$ | | 6(3a+2)=2(4a+11) | | 4(x+1)=2(5x-6) | | 2(3x+7)=4(x+23) | | 8(p-2)=5(p+13) | | 4(g+1)=8(g-8) | | 6(a+2)=2(a+16) | | 4(x+1)=2(x+20) | | 3m+8=-5m-64 | | -k+5=3k-19 | | 5(a+2)-3(a-1)=3 | | X+8/x-2=1+4x/x-2 | | -7(a-4)=14 | | 7(x-10)=5x | | a?(?7a?3)=0 | | z^z^-8z=0 | | 3d-4d+8d=28 | | y-2/3=6 | | 2x+x+x+x=470 | | 4x-4=-5(7x-6)+83 | | (32/x)+6x=90 | | 32/x+6x=90 | | (-17-3r/2)=-19 | | (3-x)(4-x)-2=0 | | 1x^2-7x+2=-8 | | x4-15x2=16 |

Equations solver categories